Effect Of Blood Storage Conditions On The Integrity Of Human Dna (Applied Biological Research, 2019)
A study was performed in blood samples, collected from 15 healthy  individuals during July to December 2017, to evaluate the integrity of DNA  by preserving blood samples at three temperatures i.e. 4, -20 and -80ºC as  against the fresh sample (control) for an incubation period of 30 days. DNA  was extracted by standard protocol of phenol-chloroform and salting out  method. The effect of temperature on DNA quality and quantity was  analyzed spectrophotometerically, followed by amplification of Cytochrome  p450 1A1 (CYP1A1) gene. In this prognosis, the study revealed that higher  purity was attained at 4ºC, yield and concentration at -20ºC on extraction by  phenol-chloroform. On contrary, in salting out method maximal yield and  concentration was acquired at 4ºC and purity at -20ºC. Comparison of  methods showed that phenol-chloroform method gave best result. DNA  obtained from preserved blood samples is appropriate for amplification and  further studies.
Keywords: CYP1A1; DNA analysis; PCR; phenol-chloroform; salting out